Parametric Study of a Plunging NACA0012 Airfoil - Camacho, E. A. R. (2022)
Natural flight has always been the source of imagination for the Human being, but reproducing the propulsive systems used by animals is indeed complex. New challenges in today’s society have made biomimetics gain a lot of momentum because of the high performance and versatility these systems possess when subjected to the low Reynolds numbers effects. The main objective of the present work is the computational study of the influence of the Reynolds number, frequency and amplitude of the oscillatory movement of a NACA0012 airfoil in the aerodynamic performance for a constant angle of attack over time. The thrust and power coefficients are obtained which together are used to calculate the propulsive efficiency. The simulations were performed using ANSYS Fluent with a RANS approach for Reynolds numbers between 8,500 and 34,000, reduced frequencies between 1 and 5, and Strouhal numbers from 0.1 to 0.4. The aerodynamic parameters were widely explored as well as their interaction, obtaining optimal operational condition zones for the different Reynolds numbers studied.